Pengaruh Kepuasan Kebutuhan Terhadap Motivasi Kerja dan Kinerja Karyawan Pada PT. Bahari Prima Manunggal - Risky Wibowo (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
One of the top priorities of the company is to ensure the happiness and job satisfaction of its employees. If workers are unhappy and frustrated because their needs are not being met, they will not be able to give their full attention to their tasks. On the other hand, when people feel that their needs are being met, they become more motivated to do their best work. Thus, this study aims to investigate the extent to which the satisfaction of needs influences work motivation and employee performance at PT Bahari Prima Manunggal. The study uses quantitative research methods by distributing questionnaires to the employees of PT Bahari Prima Manunggal. The findings of the study indicate that the satisfaction of needs has a simultaneous influence on work motivation and employee performance. Therefore, it can be inferred that if the needs of the employees at PT Bahari Prima Manunggal are met, they tend to be more motivated to perform their best. Thus, this research hopes to encourage PT Bahari Prima Manunggal to remain committed to prioritizing the satisfaction of its employees' needs in order to produce optimal performance.